The impact of a HIV/AIDS diagnosis on individuals’ mental health : an overview - Natalya Maurice,; Sam, Jeng Mun (Penerbit Universiti Kebangsaan Malaysia, 2022)
This research was undertaken to understand the thought process and perspectives, emotional experiences, and social life of Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (HIV/AIDS) patients who are living in Malaysia. HIV/AIDS can be deemed as a taboo subject especially in Malaysia because those affected by this disease are stigmatized and neglected by the community. Therefore, this attitude of the community has impacted the well-being and mental health of these patients. Rates of mental health problems are higher among both people vulnerable to acquiring HIV and people living with HIV/AIDS (PLHIV), compared with the general population. The difficulties experienced by these patients are mainly focused on the prejudice experienced among family members and managing sexual partnerships. In Malaysia, past research has been done on the psychosocial health conditions and HIV infection among homosexual men, however it is evident that HIV/AIDS can stem from various sources and therefore, a different population which are women should be researched on as well. Therefore, research has shown that women experience higher levels ofstigma and religious well-being as compared to men.